HORROR VACUI: THE MEANING CRISIS OF THE GLOBALIZED WORLD (THE CASE OF THE EUROPEAN UNION). A JUNGIAN APPROACH - Mihai NOVAC (Challenges of the Knowledge Society)
In its widest acceptation, globalization amounts to a progressive ‘interdependentization’ of the various areas, levels and regions of human civilization. On account of globalization we are much more prone to becoming one, i.e. Humanity, than in the previous epochs. But what does this mean or, in other words, what is the envisioned shape of this One humanity is heading toward in the context of globalization? Is there in fact any meaning to it? On closer examination, we might find that the issue of meaning was not very much addressed in the discussions concerning globalization; certainly, it is not a major issue on the agenda of the institutions impactful upon this process. If it did make the object of someone’s preoccupations, it was rather only of certain fringe thinkers, political and economic authorities tended to ignore, given that there were always more immediate and practical concerns at hand. However, an unasked question provides no answers and the lack of answers in this respect is very dangerous as it involves the risk of creating, willingly or not, a world without meaning. Socio-cultural arguments in this respect are there to be found by anyone willing to throw an unbiased look at our post-modern history: the industrial and technical revolutions went hand in hand with an over-instrumentalization of our Weltanschauung that, along with its obvious positive consequences, brought along homogenization, massification and alienation, in other words, lack of meaning. The European Union, for example, has just started facing the practical consequences of ignoring this apparently purely theoretical problem: its current legitimacy crisis, in favor of its more traditional state-nationalist counterparts, can be taken as a symptom thereof. This paper is, first, an attempt at asking the question of meaning in the context of globalization and, second, to provide it with an answer (mostly, but not exclusively, on the basis of Jung’s analytical psychology). The answer might prove unsatisfactory but, on the other hand, as probably with most meaningful issues, the question itself is much more essential than the answer.